Bibliometric Analysis: Phenomenon of Job Hopping Among Millennials - Eldiana, Marisa Putri; Herdiana, Indri (STIE Ekuitas, 2025)
Introduction/Main Objectives: This study examines the growing phenomenon of job hopping among millennials, driven by the need for work-life balance, flexibility, and career development. It further analyzes the implications of frequent job transitions for both organizations and individual employees Background Problems: The job hopping phenomenon that is rampant among millennials, driven by career dissatisfaction and lack of work flexibility, has resulted in high recruitment costs, unstable work culture, and decreased work productivity. Novelty: Uses bibliometric analysis, this study adopts a methodological approach that has not been widely used in previous research to examine the phenomenon of job hopping among millennials. This report maps research patterns since 2018, finds gaps in the long-term effects of job hopping, and provides recommendations for employers in creating data-driven employee retention strategies using data from VOSviewer and Scopus. Research Methods: The methods used in this study include descriptive methods and quantitative methods. This study also uses Scopus publication data and VOSviewer software for bibliometric analysis, including co-occurrence, temporal trends, and keyword networks. Finding/Results: The results indicate that dominant themes in the literature include career development, work flexibility, and job satisfaction. They also highlight a growing research focus on job hopping since 2018, particularly in countries such as the United States, India, and the United Kingdom. Conclusion: This study provides practical implications in the form of data-based employee retention strategy recommendations to reduce turnover (job hopping) and increase loyalty, while also offering insights for further research on the long-term impact of job hopping.